Inter-individual performance differences in the stop-signal task are associated with fibre-specific microstructure of the fronto-basal-ganglia circuit in healthy children. (September 2021) - Singh, Mervyn; Fuelscher, Ian; He, Jason; Anderson, Vicki; Silk, Timothy J.; Hyde, Christian
Abstract: Previous Diffusion Tensor Imaging (DTI) studies in children suggest that developmental improvements in inhibitory control is largely mediated by the degree of white matter organisation within a right-lateralised network of fronto-basal-ganglia regions. Recent advances in diffusion imaging analysis now permit greater biological specificity, both in identifying specific fibre populations within a voxel, as well as in the underlying microstructural properties of that white matter. In the present work, employing a novel fixel-based analysis (FBA) framework, we aimed to comprehensively investigate microstructure within the fronto-basal-ganglia circuit in childhood, and its contribution to inhibition performance. Diffusion MRI data were obtained from 43 healthy children and adolescents aged 9–11 years (10.42 ± .41 years, 18 females). Response inhibition for each participant was assessed using the Stop-signal Task (SST) and quantified as a Stop–Signal Reaction Time (SSRT). All steps relevant to FBA were implemented in MRtrix3Tissue, a fork of the MRtrix3 software library. The fronto-basal-ganglia circuit were delineated using probabilistic tractography to identify the tracts connecting the subthalamic nucleus, pre-supplementary motor area and the inferior frontal gyrus. Connectivity-based fixel enhancement (CFE) was then used to assess the association between fibre density (FD) and fibre cross-section (FC) with inhibitory ability. Significant negative associations were identified for FD in both the right and left fronto-basal-ganglia circuit whereby greater FD was associated with better inhibition performance (e.g., reduced SSRTs). This effect was specifically localised to clusters of fixels within white matter proximal to the right subthalamic nucleus. We did not report any meaningful associations between SSRT and FC. Whilst findings are broadly consistent with prior DTI evidence, current results suggest that SSRT is predominantly facilitated by subcortical microstructure of the connections projecting from the subthalamic nucleus to the cortical regions of the network. Our findings extend current understanding of the role of white matter in childhood response inhibition.